Bud Tumantangis: A Bangsa Sug Historic-Societal Relevance - Sajan, Alkinor R. (HM Publisher, 2021)
The history of one’s nation is the core value of its people. It reflects the totality of their personal identity, their culture, their ways of life, and the way they would be treated by others. Sulu is not an exemption, in fact, its history had been long eyed hitherto by most of the world’s historians due to the unique and glorious but controversially misconceived records of the Tausugs. These records however, Vis-à-vis the Bud Tumantangis’ core value. This paper aims to elucidate the name Bud Tumantangis and edify misconception of its true meaning. The idea of “Crying Mountain” doesn’t fit it to be the pride of the people that needs to be deep-sixed. And for it to be a pride does not mean only a mere emblem but a total relevance as well.